Organ preserving laparoscopic resection of bladder rhabdomyosarcoma in a child - Jayakumar TK; Kirtikumar J. Rathod; Taruna Yadav; Arvind Sinha; Mritunjay Kumar; Poonam Elhence (Journal of Pediatric Surgery Case Reports, 2021)
Bladder rhabdomyosarcoma (RMS) in children, at presentation are often large, situated in close proximity to vital structures. This makes the surgical resection challenging. Hence, chemoradiotherapy is often used first. For those tumors which are amenable for resection, laparoscopy can serve as a better alternative. A 5-year-old boy presented with lump in the abdomen. MRI revealed a solid tumor of size 4.8 × 4.3 × 5.3 cms arising from dome of bladder. Tru-cut biopsy of the tumor showed features of RMS, after which VAC (Vincristine, Actinomycin-D, Cyclophosphamide) chemotherapy was started. By the end of two cycles of chemotherapy, patient required hospital admission multiple times due to chemotherapy toxicity. Review imaging of the tumor showed >60% reduction in size. Laparoscopic bladder preserving partial cystectomy was done. Post-operatively patient was discharged after six days. During follow-up, patient had no urinary symptoms. The resected specimen had tumor cells at inferior margin. Adjuvant chemotherapy course was completed. Two years after the surgery, patient remains free of recurrence. Laparoscopy serves as a good alternative to open surgery for bladder RMS surgeries. Laparoscopic bladder preserving surgery can be done with good access, limiting the operative morbidity. Patients can benefit from smaller scars and speedy post-operative recovery.